Correction to: Diacerein improves liver fibrosis, steatosis, and atherosclerosis in ApoE knockout mice - Jie-Eun Lee; Isom Jin; Jung-Jae Lee; Jisu Jung; Jee-In Lee; Bo-Rahm Kim; Tae Jung Oh; Yun Kyung Lee; Sung Hee Choi (Journal of Molecular Medicine, 2026)

Diacerein improves liver fibrosis, steatosis, and atherosclerosis in ApoE knockout mice - Jie-Eun Lee; Isom Jin; Jung-Jae Lee; Jisu Jung; Jee-In Lee; Bo-Rahm Kim; Tae Jung Oh; Yun Kyung Lee; Sung Hee Choi (Journal of Molecular Medicine, 2026)
Non-alcoholic fatty liver disease and atherosclerosis may share a common pathogenesis involving chronic IL-1β-induced inflammation. We aimed to evaluate the efficacy of diacerein, an IL-1 pathway inhibitor, in improving liver fibrosis, steatosis, and atherosclerosis in apolipoprotein E-knockout (apoE k/o) mice. ApoE k/o mice fed a high-fat diet (HFD) were divided into three groups based on diacerein dosage. Liver fat accumulation and fibrosis severity were compared across groups, along with changes in the expression of genes related to lipid metabolism and fibrosis. Atherosclerotic burden in the aorta was evaluated via en face analysis, and the related signaling pathway was verified in vitro. Diacerein treatment reduced the amount of collagen fibers and fat accumulation in the liver in a dose-dependent manner as well as fibrosis-related gene expression. Atherosclerotic plaque burden in the aorta showed a decreasing trend with diacerein treatment, accompanied by reduced expression of pro-inflammatory cytokines, including TNF-α. Diacerein treatment ameliorated liver steatosis/fibrosis and showed beneficial effects on atherosclerosis-related mechanisms in HFD-fed apoE k/o mice. Given its dual anti-inflammatory and anti-fibrotic actions, diacerein represents a promising therapeutic candidate for metabolic disorders characterized by chronic inflammation. Key messages We analyzed the effects of diacerein on liver fibrosis, steatosis, and atherosclerosis in apolipoprotein E knockout (apoE k/o) mice. Diacerein reduced fat accumulation in the liver and collagen fibers in the liver. It decreased the expression of genes related to fibrosis and the burden of atherosclerotic plaque in the aorta. The expression of pro-inflammatory cytokines was reduced. Treatment of apoE knockout mice fed an HFD with diacerein effectively ameliorated liver steatosis/fibrosis and atherosclerosis. Graphical Abstract

Environment-responsive phase transformation of Ni-modified cobalt phosphate aerogels for durable hydrogen evolution in freshwater and seawater - Younghun Kim; Sang-Hyun Kim; Jiseung Kim; Wonjun Lee; Hyun Jee Heo; In Hye Kwak; Vinayak G. Parale; Hyung-Ho Park (Desalination, 2026)

The role of phospholipase A2-modified milk polar lipid in gluten network stabilization and bread volume enhancement - Yebeen Kim; Yerim Na; In kyu Lim; Yubeen Lee; Jee-Young Imm (Food Bioscience, 2025)

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Evaluating ripeness in post-harvest stored kiwifruit using VIS-NIR hyperspectral imaging - Jeong-Eun Lee; Min-Jee Kim; Bo-Yeong Lee; Lee Jong Hwan; Ha-Eun Yang; Moon S. Kim; In Geun Hwang; Cheon Soon Jeong; Changyeun Mo (Postharvest Biology and Technology, 2025)

Hepatocyte-specific RIG-I loss attenuates metabolic dysfunction-associated steatotic liver disease in mice via changes in mitochondrial respiration and metabolite profiles - Jin Kyung Seok; Gabsik Yang; Jung In Jee; Han Chang Kang; Yong-Yeon Cho; Hye Suk Lee; Joo Young Lee (Toxicological Research, 2024)

TRPM7 Mediates Neuropathic Pain by Activating mTOR Signaling in Astrocytes after Spinal Cord Injury in Rats - In Yi Kim; Chan Sol Park; Kyung Jin Seo; Jee Youn Lee; Tae Young Yune (Molecular Neurobiology, 2024)

Developing a sorptive material of cadmium from pyrolysis of hen manure - Jae-In Lee; Dongho Choi; Seungwon Kim; Jee Young Kim; Seong-Jik Park; Eilhann E. Kwon (Chemosphere, 2024)

TRPM7 Mediates BSCB Disruption After Spinal Cord Injury by Regulating the mTOR/JMJD3 Axis in Rats - Chan Sol Park; Jee Youn Lee; Kyung Jin Seo; In Yi Kim; Bong Gun Ju; Tae Young Yune (Molecular Neurobiology, 2024)

Anti-inflammatory and relaxation effects of Ulmus pumilla L. on EGF-inflamed bronchial epithelial and asthmatic bronchial smooth muscle cells - In-Seung Lee; Yeonjung Choi; Wona Jee; Jihyuk Park; Hyungsuk Kim; Kwanil Kim; Hee-Jae Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2024)

Hospital admission risks and excess costs for neurological symptoms attributable to long-term exposure to fine particulate matter in New York State, USA - Jieun Min; Whanhee Lee; Michelle L. Bell; Yijun Kim; Seulkee Heo; Ga Eun Kim; Jee Hyun Kim; Ji Young Yun; Soo In Kim; Joel Schwartz; Eunhee Ha (Environmental Research, 2023)

Effects of the DNA repair inhibitors, cytosine arabinoside and 3-aminobenzamide, on the frequency of radiation-induced micronuclei, nuclear buds, and nucleoplasmic bridges - Yoon Hee Cho; Yang Jee Kim; Sunyeong Lee; Kyung-in Joung; Hai Won Chung; Sunmi Kim; Su Young Kim (Genes & Genomics, 2020)

Histone deacetylase inhibitor CG200745 ameliorates high-fat diet-induced hypertension via inhibition of angiotensin II production - Ga-Eun Yoon; Jin Ki Jung; Yun-Han Lee; Byeong-Churl Jang; Jee In Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)
Obesity is growing rapidly worldwide due to consumption of westernized diet and lack of exercise. Obesity is one of the major risk factors of hypertension. The novel histone deacetylase (HDAC) inhibitor CG200745 was originally developed to treat various cancers. Previous studies showed that CG200745 attenuated hypertension through inhibition of cardiac hypertrophy and fibrosis in deoxycorticosterone acetate-induced hypertensive rat. The purpose of this study is to investigate the role and underlying mechanism of CG200745 in high-fat diet (HFD)-induced hypertension. Nine-week old C57BL/6 mice were fed a normal diet (ND) or HFD for 17 weeks. Each group of mice was treated with vehicle or CG200745 by intraperitoneal injection for 9 days. HFD group showed higher body weight, blood pressure (BP), HDAC activities, angiotensinogen and renin expressions in kidney, angiotensin-converting enzyme (ACE) expression in the lung, serum angiotensin II (Ang II) concentration, and myosin light chain 20 (MLC 20 ) phosphorylation in mesenteric artery compared with ND group. CG200745 lowered BP, HDAC activity, renin and angiotensinogen in the kidney, ACE in the lung, serum Ang II level, and phosphorylation of MLC 20 in HFD group. In conclusion, CG200745 ameliorated HFD-induced hypertension through inhibition of HDAC/Ang II/vascular contraction axis. Our results offer CG200745 as a novel therapeutic option for HFD-induced hypertension.

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Efficient spoofing identification using baseline vector information of multiple receivers - Seong-Hun Seo; Byung-Hyun Lee; Sung-Hyuck Im; Gyu-In Jee; Kwan-Sung Kim (GPS Solutions, 2018)

Phentermine induces conditioned rewarding effects via activation of the PI3K/Akt signaling pathway in the nucleus accumbens - Sa-Ik Hong; Min-Jung Kim; In-Jee You; Seung-Hwan Kwon; Shi-Xun Ma; Ji-Young Hwang; Jee-Yeon Seo; Yong-Hyun Ko; Bo Ram Lee; Seok-Yong Lee; Choon-Gon Jang (Psychopharmacology, 2016)

Bee Venom Acupuncture Alleviates Experimental Autoimmune Encephalomyelitis by Upregulating Regulatory T Cells and Suppressing Th1 and Th17 Responses - Min Jung Lee; Minhee Jang; Jonghee Choi; Gihyun Lee; Hyun Jung Min; Won-Seok Chung; Jong-In Kim; Youngheun Jee; Younbyoung Chae; Sung-Hoon Kim; Sung Joong Lee; Ik-Hyun Cho (Molecular Neurobiology, 2016)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Artificial neural networks for predicting DGPS carrier phase and pseudorange correction - Arif Indriyatmoko; Taesam Kang; Young Jae Lee; Gyu-In Jee; Yong Beom Cho; Jeongrae Kim (GPS Solutions, 2008)

Morphotaxonomy of the Genus Spirogyra (Zygnemataceae, Chlorophyta) in Korea - Jee-Hwan Kim; Young-Hwan Kim; In-Kyu Lee (Algae, 2004)

Assessing competence for adventitious shoot formation in hypocotyl explant cultures fromCatharanthus roseus cultivars - Pil -Son Choi; Soo -Young Lee; Hwa -Jee Chung; Dong -Soo In; Dong -Wook Choi; Jang Ryol Liu (Journal of Plant Biology, 2003)

Characterization and developmental expression of single-stranded telomeric DNA-binding proteins from mung bean (Vigna radiata) - Jee Ho Lee; Jun Hyun Kim; Woo Taek Kim; Bin G. Kang; In Kwon Chung (Plant Molecular Biology, 2000)